Ammonium Oxathioamidate - M. Carla Aragoni; David B. Cordes; Anna Pintus; Enrico Podda; Riccardo Serra; Alexandra M. Z. Slawin; J. Derek Woollins; Massimiliano Arca (Molbank)
Ammonium oxathioamidate (1) was synthesised by the reaction between O-ethyl-thioxamate (oxalic acid-1-amide-2-O-ethyl ester) and ammonium hydrogen carbonate in water solution. Compound 1 was fully characterised by both microanalytical (elemental analysis, melting point determination) and spectroscopic means (FT-IR and NMR spectroscopy). Crystals suitable for single-crystal X-ray diffraction were isolated by slow evaporation of an ethanol solution of the compound. The analysis of the crystal packing reveals the prominent role exerted by intermolecular hydrogen bonding (HB) and chalcogen bonding (ChB) interactions.